2002
DOI: 10.4049/jimmunol.168.7.3641
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reversal of Established Autoimmunity upon Transient Blockade of the LFA-1/Intercellular Adhesion Molecule-1 Pathway

Abstract: Transgenic models and administration of mAbs directed against the LFA-1/intercellular adhesion molecule 1 (ICAM-1) pathway have shown that these costimulatory molecules play a key role in generating effector cells mediating inflammatory responses. In this report, durable remission of recent diabetes in nonobese diabetic (NOD) mice was induced by transient expression of an immunoadhesin gene encoding the soluble form of ICAM-1 (sICAM-1/Ig). A single i.v. injection of an adenovirus vector encoding the immunoadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
2
29
3
Order By: Relevance
“…Thus LFA-1 may play a role in trafficking to or retention of CD4+ NKT cells by the liver, or their proliferation once there. In contrast Moriyama et al [59] and Bertry-Coussot et al [60] have shown that the transient blockade of LFA-1/ICAM pathway leads to induction of tolerance and long term reversal of established autoimmunity in NOD mice. However in our natural history study, we have shown that like NKT cell expression, LFA-1 expression is also reduced in various organs and upon immunization of the NOD mice with interventions that prevent the disease, increase both NKT cell as well as LFA-1 transcript expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus LFA-1 may play a role in trafficking to or retention of CD4+ NKT cells by the liver, or their proliferation once there. In contrast Moriyama et al [59] and Bertry-Coussot et al [60] have shown that the transient blockade of LFA-1/ICAM pathway leads to induction of tolerance and long term reversal of established autoimmunity in NOD mice. However in our natural history study, we have shown that like NKT cell expression, LFA-1 expression is also reduced in various organs and upon immunization of the NOD mice with interventions that prevent the disease, increase both NKT cell as well as LFA-1 transcript expressions.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of two of these, LFA-1 and CD44, was shown to be up-regulated in lupus and was correlated with disease activity (19,20). LFA-1 on T cells interacts with ICAM-1 on APC, and a blockade of this interaction induced the remission of diabetes in NOD mice (23). CD44 was shown to support proliferation by apposition of protein kinases for the initiation of signaling via the TCR/CD3 complex (30).…”
Section: Discussionmentioning
confidence: 99%
“…The blockade or down-regulation of these adhesion and costimulatory molecules has been shown to be beneficial in various autoimmune diseases, including lupus (23)(24)(25)(26).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…For instance, loss of LFA-1 expression in a lupus mouse model (MRL/MPJ-Fas (Ipr) signifi cantly inhibits the development of infl ammatory disease (Kevil et al, 2004) and treatment of NZB/NZW F-1 lupus mice with blocking LFA-1 antibodies inhibits autoantibody production characteristic of lupus (Connolly et al, 1994). LFA-1-blocking antibodies also inhibit the development of autoimmune diseases such as diabetes (Bertry-Coussot et al, 2002), experimental autoimmune encephalitis (EAE) (Gordon et al, 1995) and glomerulonephritis (Nishikawa et al, 1993) in different animal models. All these data indicate that incremented LFA-1 function promotes autoimmune disorders, whereas the contrary occurs when LFA-1 function decreases.…”
Section: Discussionmentioning
confidence: 99%